TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK MASSANRA GALUNG (GADAI) DI DESA TETEWATU KECAMATAN LILIRILAU KABUPATEN SOPPENG - Sulfahmi 10100119066; Musyfikah Ilyas; Suriyadi Suriyadi (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
Abstract This thesis is entitled "An Overview of Islamic Law Against the Practice of Massanra Galung (Pawn) in Tetewatu Village, Lilirilau District, Soppeng Regency." The objectives of this study are: 1). To find out the practice of Massanra Galung (Pawn) in Tetewatu Village, Lilirilau District, Soppeng Regency. 2). To find out how the views of Islamic law regarding the practice of Massanra Galung (Pawn) in Tetewatu Village, Lilirilau District, Soppeng Regency.This type of research is classified as qualitative, the research data obtained directly from the results of community interviews by paying attention to several aspects that are relevant to the issues discussed.The results of this study indicate that 1). The practice of massanra galung (pawning) in Tetewatu Village, Lilirilau District, Soppeng Regency where the practice carried out by the people of Tetewatu Village has 3 factors that encourage them to do the pawning, namely: habitual factors, wanting to help, and commercial factors. The distribution of profits obtained from the mortgaged rice fields will be divided in 2 between the pawn giver (rahin) and the pawn recipient (murtahin). The pawn deadline will be carried out in accordance with the results of the agreement. 2). The view of Islamic law on the practice of massanra galung (Pawn) in the village of Tetewatu, the community has followed the pillars and conditions for legitimacy in Islamic law, although it is still not perfect in the contract agreement. Regarding the use of pawned items that occur in the Tetewatu village community, namely the pawn recipient (murtahin) completely surrenders to the pawn giver (rahin) himself to manage himself.The implications of this research are: 1) It is expected that the pawn giver will include a land certificate as collateral, and be consistent with the mortgage deadline. 2) It is expected that religious leaders will provide understanding to the Tetewatu village community about how to carry out pawn transactions in accordance with Islamic law, even though they have carried out according to the pillars and conditions for legitimacy of pawning. Keywords: Review of Islamic Law, Galung Massanra practice.